The hybrid non-ethylene and ethylene ripening response in kiwifruit (Actinidia chinensis) is associated with differential regulation of MADS-box transcription factors. Issue 1 (December 2015) - McAtee, Peter; Richardson, Annette; Nieuwenhuizen, Niels; Gunaseelan, Kularajathevan; Hoong, Ling; Chen, Xiuyin; Atkinson, Ross; Burdon, Jeremy; David, Karine; Schaffer, Robert
Abstract Background Ripening in tomato is predominantly controlled by ethylene, whilst in fruit such as grape, it is predominantly controlled by other hormones. The ripening response of many kiwifruit (Actinidia ) species is atypical. The majority of ripening-associated fruit starch hydrolysis, colour change and softening occurs in the apparent absence of ethylene production (Phase 1 ripening) whilst Phase 2 ripening requires autocatalytic ethylene production and is associated with further softening and an increase in aroma volatiles. Results To dissect the ripening response in the yellow-fleshed kiwifruitA. chinensis ('Hort16A'), a two dimensional developmental stage X ethylene response time study was undertaken. As fruit progressed through maturation and Phase 1 ripening, fruit were treated with different concentrations of propylene and ethylene. At the start of Phase 1 ripening, treated fruit responded to ethylene, and were capable of producing endogenous ethylene. As the fruit progressed through Phase 1 ripening, the fruit became less responsive to ethylene and endogeneous ethylene production was partially repressed. Towards the end of Phase 1 ripening the fruit were again able to produce high levels of ethylene. Progression through Phase 1 ripening coincided with a developmental increase in the expression of the ethylene-unresponsive MADS-boxFRUITFUL- like gene (FUL1 ). The ability to respond to ethylene however coincided with a change in expression of another MADS-box geneSEPALLATA4 /RIPENING INHIBITOR -like (SEP4/RIN ). The promoter ofSEP4/RIN was shown to be transactivated by EIN3-like transcription factors, but unlike tomato, not by SEP4/RIN itself. Transient over-expression ofSEP4/RIN in kiwifruit caused an increase in ethylene production. Conclusions These results suggest that the non-ethylene/ethylene ripening response observed in kiwifruit is a hybrid of both the tomato and grape ripening progression, with Phase 1 being akin to theRIN /ethylene inhibitory response observed in grape and Phase 2 akin to theRIN -associated autocatalytic ethylene response observed in tomato.